2013
DOI: 10.1074/jbc.m113.452516
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Metabolic Effects of a Probiotic via Butyrate-induced GLP-1 Hormone Secretion

Abstract: Background:The prescription of probiotics as obesity and diabetes therapy is limited because of insufficient efficacy data and lack of understanding of their mechanism of action. Results: The probiotic VSL#3 prevents obesity and diabetes in mice via induction of butyrate and GLP-1. Conclusion: Probiotics modulate the gut flora to elicit beneficial metabolic effects. Significance: Administration of probiotics represents a viable treatment option for obesity and diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
419
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 590 publications
(439 citation statements)
references
References 49 publications
11
419
1
8
Order By: Relevance
“…Our findings are consistent with prior observations that rodents fed VSL#3 (12) and other single strain probiotic supplements (24)(25)(26)(27) gained less body mass and fat mass during high-fat feeding compared to controls (12). Our findings are also consistent with recent observations (9) that young, healthy subjects consuming a single probiotic strain (Lactobacillis casei Shirota) gained less body and fat mass during a high-fat diet compared with placebo.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our findings are consistent with prior observations that rodents fed VSL#3 (12) and other single strain probiotic supplements (24)(25)(26)(27) gained less body mass and fat mass during high-fat feeding compared to controls (12). Our findings are also consistent with recent observations (9) that young, healthy subjects consuming a single probiotic strain (Lactobacillis casei Shirota) gained less body and fat mass during a high-fat diet compared with placebo.…”
Section: Discussionsupporting
confidence: 83%
“…Pyruvate oxidation was used to assess the activity of pyruvate dehydrogenase (PDH), the enzyme that catalyzes the oxidation of pyruvate and the provision of glucose-derived acetyl CoA to the TCA. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]-pyruvate oxidation was assessed in a similar manner to fatty acid oxidation with the exception that pyruvate was substituted for BSA-bound palmitic acid. All samples were run in triplicate and data were normalized to total protein content and expressed in nmol/mg protein/h.…”
Section: Serum Endotoxin Was Measured With a Pyrogenementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, organic acids in feces promote elimination of Escherichia coli O-157 (29). Considering these roles of organic acids in feces and our findings, the low fecal levels of organic acids might be harmful by causing deterioration of glycemic control through the reduction of incretin hormone secretion after a meal and increased susceptibility to infection in type 2 diabetic patients (28,30). Our data showed that the level of fecal total organic acids correlated closely with carbohydrate intake, and negatively with total fat intake and saturated fatty acid intake.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were observed by Yadav et al, who found that administration of the probiotic VSL#3 prevented and treated obesity and diabetes in a number of different murine models through modulation of the gut microbiota. In particular, an increase in the number of butyrate-producing bacteria was linked with enhanced secretion of the hunger-reducing hormone GLP-1 as well as upregulation of genes involved in GLP-1 synthesis and excretion [127]. McNulty et al observed that, in gnotobiotic mice harbouring a 15-member model human gut microbial community, introduction of 5 probiotic strains isolated from a fermented milk product did not significantly alter the composition of the intestinal microbiota but instead increased the expression of microbial genes involved in carbohydrate and nucleotide metabolism while decreasing expression of genes involved in the metabolism of lipids and amino acids [128].…”
Section: Modulation By Probioticsmentioning
confidence: 99%